IMPLEMENTASI IMPORTANCE PERFORMANCE ANALYSIS (IPA) DALAM MENGEVALUASI KUALITAS PELAYANAN INFRASTRUKTUR RUAS JALAN NASIONAL DI KOTA KUPANG - Dwy Putri Sutanti; Kusa Bill Noni Nope; Amandus Jong Tallo (STKIP PGRI Situbondo, 2026)
National road infrastructure plays a strategic role in supporting economic, social, and cultural activities within a region. The quality of road services should be reflected not only in their physical condition but also in the perceptions and satisfaction of road users as the primary beneficiaries. However, most evaluations have focused primarily on technical aspects, often overlooking user experiences and expectations. This study evaluates the quality of national road infrastructure services in Kupang City based on user perceptions and satisfaction. A quantitative approach was applied involving 200 respondents of productive age from various backgrounds. The assessment covered five main variables: road conditions, complementary structures, road equipment, roadside area utilisation, and maintenance services. Data were analysed using the Importance Performance Analysis (IPA) method to measure the level of conformity between performance and importance and to identify service improvement priorities. The findings reveal that nine service attributes require improvement due to gaps between user expectations and perceived performance. Cartesian diagram analysis further identified four priority attributes: properly functioning drainage channels to prevent flooding during rainfall, availability of safety barriers on steep road sections, presence of green trees to reduce heat and improve air quality, and timely repair of road damage.These results highlight critical service aspects most strongly perceived by users and provide a basis for road operators to develop more responsive, targeted, and sustainable infrastructure service improvement strategies.